Exploring azole antifungal drug resistance in Aspergillus fumigatus with special reference to resistance mechanisms. (May 2014) - Chowdhary, Anuradha; Sharma, Cheshta; Hagen, Ferry; Meis, Jacques F
ABSTRACT: : Aspergillus fumigatus, a ubiquitously distributed opportunistic pathogen, is the global leading cause of aspergillosis. Azole antifungals play an important role in the management of aspergillosis. However, over a decade, azole resistance in A. fumigatus isolates has been increasingly reported with variable prevalence worldwide and it is challenging the effective management of aspergillosis. The high mortality rates observed in patients with invasive aspergillosis caused by azole-resistant A. fumigatus (ARAF) isolates pose serious challenges to the clinical microbiologist for timely identification of resistance and appropriate therapeutic interventions. The majority of ARAF isolates contain alterations in the cyp51A gene; however, there have been increasing reports on non -cyp51A mutations contributing to azole resistant phenotypes. This review highlights the emergence and various mechanisms implicated in the development of azole resistance in A. fumigatus . We further present recent developments related to the environmental route in the emergence of ARAF isolates and discuss the therapeutic options available.